Limiting theorems for point random fields preset on the plane - Roitgarts , A. D. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Two theorems on weak convergence of two-parameter point random fields to a point field with independent increments in Skorokhod space are given. The hypotheses of the theorems are formulated in terms of different types of compensators.